Analisis Yuridis Kekerasan Terhadap Anak Yang Menyebabkan Mati (Studi Kasus No. 175.PID.SUS/2017/PN.PMS) - Diamond Rosa Bangun (Iuris Studia: Jurnal Kajian Hukum, 2020)
The purpose of this study is to examine and analyze the factors that cause violence against children, to study and analyze criminal law policies against perpetrators of violence against children, to study and to analyze the application of law by judges to cases of violence against children. This research uses the library research method, which is conducting research to obtain primary data, namely books, laws and regulations and other main reference sources, and secondary data is additional readings such as the internet and official documents issued. by the government. Besides that, field research was also carried out by conducting interviews. The results showed that the factors causing violence against children were family economic factors, family disharmony, parental education, past experiences of parents or caregivers, community perceptions, lack of supervision (protection) of children, social environment, social media, and exploitation. child. Thus, the factors that cause child abuse are largely derived from the behavior of adults such as parents, close family members or other parties who are not willing to consciously protect the child from all the potential that allows violence against children to occur. The criminal policy against perpetrators of violence against children is good enough, but its implementation cannot be maximally implemented because people do not know the rules of law and there is a public perception that violence against children in the family sphere is an internal matter for educational reasons. In addition, evidence of violence against children is often constrained by a lack of evidence. The criminal law policy has provided legal protection for the rights of child victims of violence to ensure the participation of victims from investigation to prosecution and ensure the recovery of victims. But these policies are not fully able to guarantee a bleak future for victims who experience permanent suffering